Water pollution and cattle health risks in the Akaki River Catchment, Central Ethiopia: implications for one-health - Abosse, Jirata Shiferaw; Assefa, Samuel; Teketel, Zerihun; Efa, Debela Abdeta; Wolde, Biruk; Eregno, Fasil Ejigu (Frontiers in Water, 2025)
This study examines the toxic effects of river pollution on cattle health in Akaki River Catchment, central Ethiopia. Water and blood samples were collected from ten sampling points and four clusters, kept the first sampling point and first clusters as control. Water samples were collected from the river and analyzed for physicochemical and heavy metal parameters, while blood samples were collected from cattle and tested for heavy metal accumulation and key hematological and biochemical health indicators. Based on these analyses, the Livestock Water Pollution Index (LWPI) and Livestock Health Index (LHI) were developed to assess water quality and cattle health, respectively. The study found that LWPI values ranged from 107.16 to 429.93, with a mean value of 299.26. The LWPI exceeded safe limit (LWPI = 100) at all ten sampling points, with pollution levels increasing progressively downstream. Among the measured parameters, turbidity, lead (Pb), zinc (Zn), and cadmium (Cd) were the most significant contributors to river pollution, in that order. Blood analysis results showed that the LHI ranged between 152.48 and 290.82, with a mean value of 232.81 across all clusters. Similarly, the LHI was above the normal threshold (LHI = 100) in all clusters studied, with elevated levels also observed downstream. Lead, blood urea nitrogen (BUN), and Cd emerged as key contributors to declining livestock health, highlighting heavy metal contamination and physiological stress as major risk factors. The relationship between LWPI and LHI revealed a strong positive correlation, suggesting that river pollution significantly contributed to livestock health risks. The findings highlight risks to cattle health, with health implications for human consuming milk, meat, and its products. The study calls for the implementation of integrated one-health strategies, focusing on enforcement of regulations to reduce waste discharges to the river, provide safe water alternatives for livestock, assess human health risks from contaminated cattle products, and engage communities in sustainable practices through river stewardship programs.